Growth and lipid production of Rhodotorula glutinis R4, in comparison to other oleaginous yeasts - Maza, Debora Daniela; Viñarta, Silvana Carolina; Su, Ying; Guillamón Navarro, Jose Manuel; Aybar, Manuel Javier (Journal of Biotechnology)
Some Rhodotorula spp. have been characterized as oleaginous yeasts. Under certain culture conditions they can accumulate neutral lipids, which are mainly triglycerides (TAG). Microbial TAG that can be used as raw material for biodiesel synthesis are attractive for the biofuel industry. In this study, the ability to synthesize lipids of Rhodotorula glutinis R4, isolated in Antarctica, was compared with eight strains belonging to the genera Rhodotorula and Yarrowia with the aim of proposing a novel source of oils for biodiesel synthesis. All strains were cultured under nitrogen (N) limiting conditions and an excess of carbon (C) in the culture medium. We found that yeasts accumulated between 9–48.9 % (w/w) of lipids. Among them, R. glutinis R4 showed the highest growth (14 g L−1, μmax 0,092 h−1) and lipid production (7 g L−1; 47 % w/w). Microbial oils produced by R. glutinis R4 are similar to vegetable oils, with 61 % of oleic acid, indicating that it is adequate for biodiesel synthesis. Our results demonstrate that biodiesel derived from R. glutinis R4 complies with international fuel standards ASTM D6751 and EN 14214. Therefore, this work demonstrates that Rhodotorula glutinis R4 is a novel and valuable source of microbial oils for biodiesel synthesis. Fil: Maza, Debora Daniela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Instituto Superior de Investigaciones Biológicas. Universidad Nacional de Tucumán. Instituto Superior de Investigaciones Biológicas; Argentina Fil: Viñarta, Silvana Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Planta Piloto de Procesos Industriales Microbiológicos; Argentina Fil: Su, Ying. Consejo Superior de Investigaciones Científicas. Instituto de Agroquímica y Tecnología de Alimentos; España Fil: Guillamón Navarro, Jose Manuel. Consejo Superior de Investigaciones Científicas. Instituto de Agroquímica y Tecnología de Alimentos; España Fil: ...